Exploring The Impact Of Cross Culture Adjustment Towards Economic Growth In Malaysia - Razinda Tasnim Abdul Rahim; Mai Syaheera M. Shaari; Muhammad Aizat Md Sin (Universiti Sains Islam Malaysia, 2024)
Proceedings of the 7th International Prophetic Conference (SWAN) 2020 FPQS,Universiti Sains Islam Malaysia, 29-30 October 2020 Paper No. BI001 1-14